Effects of Rosa damascena (Damask rose) on menstruation-related pain, headache, fatigue, anxiety, and bloating: A systematic review and meta-analysis of randomized controlled trials - Seyedeh Atefeh Koohpayeh; Meimanat Hosseini; Morteza Nasiri; Masoud Rezaei (Wolters Kluwer Medknow Publications, 2021)
Recent studies have reported inconclusive results regarding the therapeutic effects of Rosa damascena on the outcomes of primary dysmenorrhea (PD) and premenstrual syndrome (PMS). Hence, this study is aimed to summarize the findings of randomized controlled trials (RCTs) regarding the effects of this treatment on menstruation-related pain as the primary outcome and menstruation-related headache, fatigue, anxiety, and bloating as the secondary outcomes. This study evaluated parallel-group and cross-over RCTs on aromatherapy, topical treatment, or oral intake of R. damascena products for the treatment groups versus placebo, nontreated, or conventional treatment groups. Seven electronic databases (Web of Science Core Collection, Scopus, Embase, CENTRAL, CINAHL, SID, and MagIran) and one search engine (PubMed) were searched from inception to January 15, 2021. Of 1468 trials found in the initial search, 983 potentially relevant articles were screened by title and abstract. After examining the full-text of 13 studies for compliance with the inclusion criteria, seven studies were considered eligible for this review. A random-effects model was used to pool the data; otherwise, a narrative summary was presented. The retrieved studies were conducted on females with PD or PMS, aged 18-35 years. The total sample size of the intervention and comparator arms was 276 and 272. The results showed that R. damascena had a nonsignificant alleviating effect on the menstruation-related pain (weighted mean difference [WMD]: −0.47; 95% confidence interval [CI]: −1.25, 0.31; P = 0.234). Such findings were also found for menstruation-related anxiety (WMD: −0.40; 95% CI: −0.91, 0.11; P = 0.125). However, the treatment significantly reduced the menstruation-related headache (WMD: −0.42; 95% CI: −0.74, −0.11; P = 0.008), fatigue (WMD: −0.48; 95% CI: −0.87, −0.09; P = 0.015), and bloating (WMD: −0.72; 95% CI: −1.21, −0.22; P = 0.005). Since R. damascena had no significant effects on menstruation-related pain and anxiety, further studies with improved methodological quality are suggested to evaluate the effects of the treatment on these symptoms, using different dosages and durations.